Cultivating Creativity: Faculty Conceptions of Creativity in Agricultural Communications Students - Courtney Gibson; Hope Hancock; Erica Irlbeck; Courtney Meyers (Journal of Applied Communications, 2018)
Creativity has been deemed as an essential skill in agricultural communications graduates by both industry and academia, and it has a pivotal role in student success within the classroom and the workforce. In order to foster students’ creative thinking skills, faculty must turn away from traditional norms of lecture-based delivery and foster an environment where students are actively creating and engaging in the learning process. The purpose of this study was to provide insight on the nature of creativity as it relates to agricultural communications curriculum—focused on pedagogical strategies and creative assessments. This qualitative case study examined how agricultural communications faculty understood and facilitated creativity within their respective classrooms using in-depth, face-to-face interviews and documents. The findings revealed a lack of a cohesive language as it relates to creativity. Additionally, the results explored different pedagogical practices that facilitate creative thinking, and the various ways faculty perceive creative assessments. Based on participants’ responses, a social constructivist alignment in the classroom could prove beneficial in fostering a creative classroom environment. Additionally, the use of scaffolding (changing the level of instructor support) has proven useful in nurturing creative thought and constructing knowledge.
Keywords: create; creativity; creative thinking; students; higher education; agricultural communication